Activity of Bidens Pilosa Herb Infussion as Antiinflammatory - Wahyuddin, Munifah; Nurdaonah, Nurdaonah; Ferawati, Ferawati (Ad-Dawaa' Journal of Pharmaceutical Sciences, 2020)
Ajeran (Bidens pilosa), traditionally, was widely used to reduce pain and inflammation. This study aims to determine the activity of Ajeran herb infusion as an anti-inflammatory. Determination of activity using 18 mice which were divided into 6 groups. Blank group (I) was given aquadest, groups II, III, IV and V were given Ajeran dry herb infusion with concentrations 10, 20, 30 and 40% w/v, respectively, and group VI was given sodium diclofenac suspension 0,195 mg/ml, each 1 ml. Inflammation induction was performed by administering eggwhite suspension 1% v/v on the sole of the left foot. Foot volume before and after induction were measured as normal and initial edema volume. After that, the mice were given treatment and measurements of foot volume again at 15, 30, 45 and 60 minutes. The test results showed that the infusion of Ajeran and diclofenac sodium could reduce edema starting at 15 minutes, which were 17.8% (II); 20.6% (III); 22.2% (IV); 25% (V); and 15% (VI). It was different with blank group, the volume of edema did not decrease (0%). At 60 minutes, the volume of edema in all groups higher decreased that at 15 minutes, namely 23.4% (I); 28.9 (II); 35.6 (III); 37% (IV); 41.7% (V); and 30% (VI). The conclusion is that the administration of Ajeran infusion can reduce the volume of edema of feet with inflammation of mice.